SEXUAL BEHAVIOR DETERMINANT FACTOR IN ADOLESCENTS IN KEBAYORAN LAMA SELATAN VILLAGE IN 2020 - Muti Afrida; Thresya Febrianti (Universitas Airlangga, 2023)
Future threats are posed by the high prevalence of risky sexual behavior in adolescents. The purpose of this study is to examine the factors influencing sexual behavior among adolescents in Kelurahan Kebayoran Lama Selatan in 2020. The research study design used a cross-sectional with a total sample of 194 respondents. The sampling technique was snowball sampling and the analysis used was descriptive. It shows that half of all adolescents have risky behavior, namely 165 people (85.1%), but a quarter of them have non-risk behavior (14.9%). The distribution of majority of respondents has peer influence 25.3%, more information sources in watching pornography on friends 43.3%, internet mass media that is often seen 36.6%, the frequency of pornography in the category is sometimes 39.7%, partner pornography when alone 24.2% and their lover/girlfriend 17.5%, the reasons for watching pornography were 28.4% of curiosity and 16.0% of sexual desire, and the role of good parents in educating children 95.4%. Sexual behavior in adolescents in Kebayoran Lama Selatan Village shows that there are still many teenagers who engage in risky sexual behavior. This research is expected to facilitate the needs of adolescents so that they can channel their energy and make good use of their free time.